2009
DOI: 10.9775/kvfd.2009.479
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Zinc Levels in Well Water in Sanliurfa and Vicinity

Abstract: Makale Kodu (Article Code): KVFD-2009-479Özet Bu çalışma Şanlıurfa ili ve ilçelerindeki 50 kuyudan temin edilen su örneklerinde çinko ve selenyum düzeylerinin belirlenmesi amacıyla yapıldı. Su örneklerindeki, çinko ve selenyum düzeyleri Plazma Optik Emisyon Spektrometresinde (ICP-OES) ölçüldü. İncelenen kuyu suyu örneklerinin %54 'ünün (>10 μg/L) kıta içi su kaynakları sınıflandırmasına göre selenyum yönünden kirli, %44'ünün (>200 μg/L) ise çinko yönünden az kirlenmiş olduğu belirlendi. Sonuç olarak, Şanlıurfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…In a study of well waters in the Urfa province (SE Anatolia), the Se levels were found to be higher than the recommended legal regulations (>0,01 mg/L) (36). The Urfa province is neighboring Diyarbakır and is close to the Euphrates.…”
Section: Samplingmentioning
confidence: 92%
“…In a study of well waters in the Urfa province (SE Anatolia), the Se levels were found to be higher than the recommended legal regulations (>0,01 mg/L) (36). The Urfa province is neighboring Diyarbakır and is close to the Euphrates.…”
Section: Samplingmentioning
confidence: 92%
“…Although it is one of the elements necessary for the human body, it is reported that high selenium ratios can cause disorders in some organs and systems. 31 According to the Bray-Curtis similarity analysis, while the degree of similarity of the months according to the physicochemical contents was determined >80 %. Also, Correspondence analysis results grouped the sampling periods in 3 different clusters for the physicochemical similarities (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Clean water (containing no heavy metal, chemical materials, or pathogen microorganisms), which is a necessity for all vital activities, should be provided for humans. Heavy metals reaching risky levels especially due to technological advancements and increasing environmental pollution, accumulate within the bodies of plants, animals, and humans and pose a threat to human health [5,6]. It is also interesting that the number of studies examining water pollution and quality from this aspect has increased in the recent period.…”
Section: Introductionmentioning
confidence: 99%